User-Centered Design for Urban Locksmiths: Integration of Design Thinking, TRIZ, NASA-TLX, and Kano-AHP Method - Huamanchumo Senador, Claribel; Manzanares Grados, Ruth Aracelis (LACCEI, 2025)
This study presents a comprehensive methodological approach based on Design Thinking and TRIZ for the user-centered design of a portable workstation aimed at residential locksmiths in the district of Comas, Lima. The research addresses the issue of high perceived workload resulting from the use of conventional tool cases that lack ergonomic criteria. Multicriteria analysis tools such as NASA-TLX were applied to assess cognitive workload, and the Kano-AHP model was used to prioritize functional attributes valued by users. Based on functional analysis and the identification of technical and physical contradictions, an ergonomic and transformable tool-carrying backpack was developed and validated through finite element simulations (FEA) and physical prototyping. The testing phase with real users showed a 50% reduction in perceived workload, significantly improving physical effort, temporal demand, and subjective performance. The integration of design methods, ergonomic evaluations, and prioritization tools proved effective in generating an innovative, context-sensitive, and technically robust solution. This approach may be replicated in other sectors of informal technical work, promoting the design of tools focused on user well-being.